Moving towards an advanced method to assess the toxicity of ceramic nanoparticles in human alveolar epithelial cells - Bessa, Maria João (2019)
The aim of this study was to investigate the in vitro toxicity of three ceramic nanoparticles in A549 cell line, a primary target during inhalation exposure.